Transformational Mentoring Experiences for First Nations Young People: A Scoping Review - Mishel McMahon; Michael Chisholm; Aldara Yenara; Tanya Garling; Werner Vogels; Julia Van-Vuuren; Corina Modderman (2023)
While Aboriginal youth mentoring has been used as a teaching process for thousands of years and the tradition continues, little attention has been paid to documenting what elements make learning experiences transformational. As part of the evaluation of the Aldara Yenara mentoring program, this Aboriginal-led scoping review examined literature about transformational mentoring programs from Canada, Australia and Aotearoa New Zealand to understand their key elements and provide guidance for future research and practice. The use of relational mapping was applied in an attempt to locate literature written by Aboriginal scholars including grey literature. Twenty-seven documents were reviewed including 20 from the peer-reviewed literature and seven acquired through the relational mapping. A total of 13 met the inclusion criteria, predominantly written by non-Aboriginal authors. Four distinct themes emerged and informed our narrative synthesis. Absent in this material, largely neither led nor owned by Aboriginal people, was any reference to connection to Country as central to Aboriginal transformational healing programs. Without Aboriginal leadership, communication and processes in these programs, there was a failure to draw on Aboriginal understandings of healing spaces. From here on in, research and practice in this area must be Aboriginal-led to ensure deeper, Aboriginal-informed understandings for First Nations transformational mentoring programs.